How to improve parenting in Hong Kong by training: the 6As Positive Parenting Program. Issue 1 (17th June 2019) - Yip, Fiona W.L.; Zelman, Diane; Low, Adrian
Abstract : Purpose: Research suggests that children in Hong Kong are at an elevated risk of emotional problems. Authoritarian parenting, a common parenting style in Hong Kong, is a critical factor associated with childhood mental health problems. The purpose of this paper is to evaluate the effectiveness of the 6As Positive Parenting Program (6As) in modifying parenting attitudes, reduction of parenting stress and increasing self-efficacy in positive parenting, among a sample of 82 Hong Kong parents. 6As focuses on prevention by instilling positive parenting beliefs and principles, thereby reducing reliance on authoritarian and related parenting styles. Design/methodology/approach: The program was evaluated using a controlled pre-post-treatment design. Outcome measures were the Chinese Child-rearing Beliefs Questionnaire, Parental Stress Scale, Parenting Self-efficacy Scale and participant feedback. ANOVA and correlation were utilized to detect treatment effects and relationships between the degree of change among measures and subscales. Findings: Relative to the control group, the 6As Positive Parenting Program significantly changed parents' parenting attitudes, reduced parenting stress and increased self-efficacy in positive parenting. In sum, 97.6 percent of the participants agreed that the program is a good fit for the Hong Kong culture. Research limitations/implications: A larger sample would have been desirable for this study. One factor that limited analyzable data was that some of the participating organizations enrolled participants into the program who did not meet research inclusion criteria. Furthermore, the size of groups varied from 5 to 16 participants, which may have produced different group dynamics that added variability to outcomes. Future 6As parenting program research should attempt to standardize group size or to directly compare the effectiveness of smaller vs larger groups. Furthermore, as noted earlier, the research was conducted during the primary school application period, which may have heightened the parenting stress for parents of younger children. Practical implications: The results suggest that an enhanced belief in authoritative, autonomy and training strategies could reduce parental stress and shift parents' attitude toward a more positive approach in child-rearing. Social implications: There is considerable need for a holistically designed parenting training that is culturally credible and sensitive. Originality/value: Findings suggest that positive parenting can enhance the parent–child relationship and reduce parental stress. The results support governmental, non-governmental organizational and community focus on positive practices for parenting training in Hong Kong.